KARSTIFICATION STUDY OF RAJAMANDALA FORMATION BASED ON HYDROGEOCHEMICAL DATA IN GUNUNG MASIGIT AND CIPTAHARJA AREA, WEST BANDUNG REGENCY, WEST JAVA - Hakim, Rahman
Karst aquifer can get contaminated easily because of open fractured system. Opportunities for contamination are increasing, because population in karst area of Padalarang is increasing rapidly. Therefore, karstification study in Gunung Masigit and Ciptaharja, West Java, becomes very important. This research was carried out using remote sensing, geochemistry, and hydrogeological methods with emphasis on hydrochemical analysis. Study area is stratigraphically located on Rajamandala Formation with constituent rocks which are limestone. Geological structure of the research area is a fold and thrust belt system. Lineament of morphology has a dominant direction northwest-southeast and northeast-southwest. Hydrogeological system of the research area is regionally controlled by the pattern of lineament with northwest-southeast direction. The mechanism for emergence of dominant karst springs controlled by contact with claystone lithology of Batuasih Formation. The karst springs in the study area have temperature of 26,8 ? – 27,3 ?, TDS 443 – 511 mg / l, and pH 6,42 – 7,39. PCO????????has a value of 1,193% – 7,673% and some springs have saturation of the mineral CaCO???? during the dry season -1,92 to - 1,55 and not saturated during the rainy season -1,43 to -1,22. PCO???????? in dry season was 1,26 – 7,67 and rainy season 1,19 – 2,82. From results of XRF analysis were known that the limestone of the study area had values of CaO 96,3 – 99,5%. Hydrochemical facies of the springs in study area is Ca-HCO???? facies, it suggests that there is interaction of limestone on the springs. Hydrogeological system in the study area is controlled by lineaments with northwest-southeast and southwest-west pattern and emergence of springs was in line density with a value of 200 – 400 / km????. Based on lithological data, the study area divided in 3 carbonate rock facies associations, namely basin margin turbidite and debrite, foreslope, and platform margin reef. Each facies association have CaO values respectively 97,4 – 99,3%, 96,3 – 98%, and 98,4 – 99,5%. Hydrochemical character of all springs in the rainy season is in condition of rapid dissolution and in dry season is in tropical springs and drip waters. Almost all climatic conditions in spring MA # 4 has a high SIcalcite value, whereas in MA # 1 has a low value SIcalcite. This condition can be caused by carbonate facies association on hydrochemical characters in each spring. Based on various results above the karst system of the study area are susceptible to surface contamination from surface activity.